Diagnostic approach and monitoring of chronic kidney disease in the primary care pediatric population - Martha I. Carrascal; Karen J. Sánchez-Acosta; Lina J. Herrera-Parra; Juan G. Cárdenas-Aguilera; Ana K. Serrano-Gayubo; Clímaco A. Jiménez-Triana; Lizbeth A. Merchán; Ana Ma. Valbuena-García; Richard Baquero-Rodríguez (Permanyer, 2024)
Chronic kidney disease (CKD) has severe consequences on the quality and expectancy of life and is considered a major health problem worldwide. This is, especially relevant in pediatric patients, as they have unique characteristics and a mortality rate 30 times higher (in advanced stages) than healthy people. This review aims to define the minimum components for the diagnostic approach and monitoring of CKD in the pediatric population from primary health care to promote comprehensive care and adequate risk management. For this purpose, we performed a systematic review of the literature with a panel of experts. Based on the evidence, to optimize the definition, diagnosis, and timely treatment of CKD in the pediatric population, we formulated 21 recommendations. These were approved by the research team and peer-reviewed by clinical experts. They will facilitate the definition of the diagnostic approach for CKD in the pediatric population in primary health-care settings, allowing for timely treatment intervention, comprehensive care, and monitoring of this disease.